2020
DOI: 10.3390/ijerph17176147
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Employees’ Perceptions of Their Work Environment: A Focus Group Perspective

Abstract: Burnout in healthcare professionals can lead to adverse effects on physical and mental health, lower quality of care, and workforce shortages as employees leave the profession. Hospice professionals are thought to be at particularly high risk for burnout. The purpose of the study was to evaluate workplace perceptions of interdisciplinary hospice care workers who provide care to patients at end of life. Six focus groups and one semi-structured interview were conducted with mixed group of social workers, manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…It is completed by the detection and problem resolution system, which supports the first system by regulating the observed shifts. Lehto et al [ 45 ] draw similar conclusions following their observation in the Midwest of the United States on the importance of being able to intervene in the determinants of work for the quality of work life. According to our observations, the first system seems to be very hampered by the dispersion of decision-making centers, which makes it very difficult to react, and by the distance from the activity, where the opportunity for field expertise and its recognition is lost.…”
Section: Discussion and Implications Of The Research Results For Work Design In Assisted Living Residencesmentioning
confidence: 57%
See 1 more Smart Citation
“…It is completed by the detection and problem resolution system, which supports the first system by regulating the observed shifts. Lehto et al [ 45 ] draw similar conclusions following their observation in the Midwest of the United States on the importance of being able to intervene in the determinants of work for the quality of work life. According to our observations, the first system seems to be very hampered by the dispersion of decision-making centers, which makes it very difficult to react, and by the distance from the activity, where the opportunity for field expertise and its recognition is lost.…”
Section: Discussion and Implications Of The Research Results For Work Design In Assisted Living Residencesmentioning
confidence: 57%
“…This only underlines the importance of continuing to study and strengthen the protective processes revealed. The recent work of Lehto et al also mentions these barriers [ 45 ], and on a related issue, a very interesting analysis of individual strategies of emotional and cognitive regulation has recently been carried out in this sense [ 46 ], which in a way recalls the work of Lazarus [ 47 ] on coping strategies in relation to stress. The latter lacks the consideration of interpersonal and organizational dynamics.…”
Section: Discussion and Implications Of The Research Results For Work Design In Assisted Living Residencesmentioning
confidence: 99%
“…Two thirds of HPs who experienced at least one meditation went on to do a meditation on their own, a finding that suggests that HPs valued having access to these meditations. We know from focus group interviews with HPs that they did not want company-sponsored personal burnout interventions to be something time consuming that HPs were expected to do on their own time [ 2 ]. For example, some HPs mentioned not wanting to have to use personal time to attend company picnics or to complete online training modules.…”
Section: Discussionmentioning
confidence: 99%
“…Focus group interviews with HPs at the same organization as the current study found that when HPs start noticing that they are feeling burned out, they take self-care steps such as mental health days to recover [ 2 ]. HPs indicated that workload and administrative demands were the major source of burnout, and that dealing with death and dying would periodically start to feel overwhelming, either because of a particularly distressing event or just unrelenting buildup [ 2 ]. The meditations in the intervention are tools HPs can use when life events present a need, such as before or after a stressful patient visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation